2014
DOI: 10.3382/ps.2014-04164
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study identifies novel single nucleotide polymorphisms associated with dermal shank pigmentation in chickens

Abstract: Shank color of domestic chickens varies from black to blue, green, yellow, or white, which is controlled by the combination of melanin and xanthophylls in dermis and epidermis. Dermal shank pigmentation of chickens is determined by sex-linked inhibitor of dermal melanin (Id), which is located on the distal end of the long arm of Z chromosome, through controlling dermal melanin pigmentation. Although previous studies have focused on the identification of Id and the linear relationship with barring and recessive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…The genome-wide study revealed that 3 SNP located at 78.5 to 79.2 Mb on the Z chromosome in the current assembly of chicken genome (galGal4) were significantly associated with dermal shank pigmentation of chickens, but none of them were located in known genes. The interval we refined was partly converged with previous results, suggesting that the Id gene is in or near our refined genome region [11]. Zhang, et al [12] investigated the genetic basis of the gray dilution phenotype in the Anti tile-like gray chicken.…”
Section: Candidate Genes For Skin Color In Farm Animals Chickensupporting
confidence: 73%
See 1 more Smart Citation
“…The genome-wide study revealed that 3 SNP located at 78.5 to 79.2 Mb on the Z chromosome in the current assembly of chicken genome (galGal4) were significantly associated with dermal shank pigmentation of chickens, but none of them were located in known genes. The interval we refined was partly converged with previous results, suggesting that the Id gene is in or near our refined genome region [11]. Zhang, et al [12] investigated the genetic basis of the gray dilution phenotype in the Anti tile-like gray chicken.…”
Section: Candidate Genes For Skin Color In Farm Animals Chickensupporting
confidence: 73%
“…This indicates ASIP participates in the regulation of skin color, which is supported by the recent study in zebrafish and avain [9,10]. Li, et al [11] used the 600K Affymetrix Axiom HD genotyping array to perform a genome-wide association study on pure lines of 19 Tibetan hens with dermal pigmentation shank and 21 Tibetan hens with yellow shank to refine the Id location. The genome-wide study revealed that 3 SNP located at 78.5 to 79.2 Mb on the Z chromosome in the current assembly of chicken genome (galGal4) were significantly associated with dermal shank pigmentation of chickens, but none of them were located in known genes.…”
Section: Candidate Genes For Skin Color In Farm Animals Chickenmentioning
confidence: 81%
“…We obtained 40 offspring, 22 of which were dwarf females with normal tails, 16 rumpless males with normal body size, and the two others were males with normal tail and normal body size. The second breed was a Jianghan chicken that had green shanks, which is a recessive trait determined by an unknown gene on the Z chromosome 14 , 42 . We obtained 39 offspring, 17 of which were rumpless and yellow-shanked males, 19 were normal tailed and green-shanked females, two were rumpless and green-shanked males, and one was a normal tailed and yellow-shanked male.…”
Section: Resultsmentioning
confidence: 99%
“…High-density ~670k genotyping arrays were used in domestic cattle to identify structural variation [39,40]. Other studies have leveraged this technology to discover and refine loci associated with production traits [41][42][43]. Based on reports from other domestic animals, coupled with preliminary analyses performed here, we anticipate similar performance and increased power for map-based studies to soon follow in the horse.…”
Section: Discussionmentioning
confidence: 91%